2022
DOI: 10.1109/tmi.2022.3143953
|View full text |Cite
|
Sign up to set email alerts
|

Joint Spine Segmentation and Noise Removal From Ultrasound Volume Projection Images With Selective Feature Sharing

Abstract: Volume Projection Imaging from ultrasound data is a promising technique to visualize spine features and diagnose Adolescent Idiopathic Scoliosis. In this paper, we present a novel multi-task framework to reduce the scan noise in volume projection images and to segment different spine features simultaneously, which provides an appealing alternative for intelligent scoliosis assessment in clinical applications. Our proposed framework consists of two streams: i) A noise removal stream based on generative adversar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Data augmentation is typically used in deep learning to increase the variety of the training dataset, and recent studies have shown the benefits of data augmentation for deep learning-based segmentation [10]. Therefore, these data augmentations, such as application of Gaussian noise, elastic transformation, rotation, and flipping have been used in stateof-the-art studies on ultrasound segmentation [11], [12], [13], [14]. However, due to the large volume of 3D+t US images available in this study and the fact that these augmentations lead to less realistic ultrasound images, data augmentation might not be beneficial, and models without augmentation were trained as well.…”
Section: Models and Trainingmentioning
confidence: 99%
“…Data augmentation is typically used in deep learning to increase the variety of the training dataset, and recent studies have shown the benefits of data augmentation for deep learning-based segmentation [10]. Therefore, these data augmentations, such as application of Gaussian noise, elastic transformation, rotation, and flipping have been used in stateof-the-art studies on ultrasound segmentation [11], [12], [13], [14]. However, due to the large volume of 3D+t US images available in this study and the fact that these augmentations lead to less realistic ultrasound images, data augmentation might not be beneficial, and models without augmentation were trained as well.…”
Section: Models and Trainingmentioning
confidence: 99%
“…For the sake of brevity, we denote the references for corresponding topics in the form of numbers in the bracket. Deep learning based segmentation model: segmentation building blocks (1) [19], [20], RNNs (2) [21], GNNs (3) [22], attention (4,5) [23], [24], Transformer (6,7) [25], [26], multi-scale (8,9) [27], [28], boundary correction block (10,11) [6], [29]; architecture, Encoder-Decoder (12) [1], detection based segmentation architecture (13)(14)(15) [19], [27], [30]- [35], generative models (16) [36]. Loss function: segmentation task oriented (17,18) [37], [38]; generative models oriented (16) [36]; supervision strategies oriented (19,20) [39], [40]; transfer learning oriented (21)(22)(23)(24) [41]-…”
Section: Loss Functionmentioning
confidence: 99%
“…Xie et al [58] applied the main task of denoising to preserve retinal structural information, where auxiliary segmentation task provided retina-related region information. Huang et al [5] applied multi-task denoising-segmentation for segmentation purpose, where the scan noise -generated from moving 2D scanning, 3D formation and anatomical plane projectionis significantly different from the non-Gaussian statistics of speckle noise.…”
Section: Loss Functionmentioning
confidence: 99%
See 2 more Smart Citations